Relationship Between Alzheimer’s Disease and the Immune System: A Meta-Analysis of Differentially Expressed Genes - Wang, Nan; Zhang, Ying; Xu, Li; Jin, Shuilin (Frontiers in Neuroscience, 2019)
Alzheimer's disease (AD) is the most prevalent form of dementia worldwide and many studies have discussed the relationship between immune system and AD pathogenesis. Here, the mendelian randomization study of differencially expressed genes based on microarray data were performed. And 9519 target genes of hippocampus in 146 subjects (73 AD cases and 73 controls) from 4 microarray data sets were compiled and differentially expressed genes with p<1.0E-4 were selected to explore the pathways analysis. The results indicated that the differentially expressed genes are significantly enriched in the neurodiseases as well as the immune system pathways.